microRNA-4701-5p protects against interleukin-1β induced human chondrocyte CHON-001 cells injury via modulating HMGA1 - Hui Zhang; Cheng Chen; Jie Song (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background miRNA-4701-5p has been reported to be a vital regulator in many diseases, including rheumatoid arthritis, and miRNA-4701-5p is evidenced to be participated in synovial invasion and joint destruction. In our report, we investigated the roles of miRNA-4701-5p in osteoarthritis (OA) and analyzed the molecular mechanism. Methods Interleukin-1β (IL-1β) was applied for stimulating human chondrocyte CHON-001 cells to establish an OA injury model. mRNA levels and protein expression were measured using qRT-PCR and western blot assay, respectively. The proliferation ability and cytotoxicity of CHON-001 cells were checked using MTT assay and lactate dehydrogenase activity. The inflammation of chondrocytes was accessed by the secretion levels of interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor (TNF)-α. The apoptosis of chondrocytes was determined by flow cytometry assay. Bioinformatics software Starbase v2.0 analyzed the functional binding sites between miRNA-4701-5p and HMGA1 and the interaction was further confirmed using dual luciferase reporter analysis. Results: miRNA-4701-5p was down-regulated in the IL-1β-stimulated chondrocytes and HMGA1 directly targeted miRNA-4701-5p. Up-regulation of miRNA-4701-5p could alleviate IL-1β-treated CHON-001 cells inflammation and apoptosis, and reversed the cell proliferation decrease and cytotoxicity increase after IL-1β treatment. Nevertheless, all the roles of miRNA-4701-5p overexpression in CHON-001 cells could be reversed by HMGA1 up-regulation. Conclusions miRNA-4701-5p could alleviate the inflammatory injury of IL-1β-treated CHON-001 cells via down-regulating HMGA1, indicating that miRNA-4701-5p/HMGA1 is a promising therapeutic target for OA.